Mycobacterium tuberculosis-Induced Upregulation of the COX-2/mPGES-1 Pathway in Human Macrophages Is Abrogated by Sulfasalazine - Wang, Wenfei; Ning, Yuping; Wang, Yejun; Deng, Guofang; Pace, Simona; Barth, Stefanie A.; Menge, Christian; Zhang, Kehong; Dai, Youchao; Cai, Yi; Chen, Xinchun; Werz, Oliver (Frontiers in Immunology, 2022)
Macrophages are the primary human host cells of intracellular Mycobacterium tuberculosis (M.tb) infection, where the magnitude of inflammatory reactions is crucial for determining the outcome of infection. Previously, we showed that the anti-inflammatory drug sulfasalazine (SASP) significantly reduced the M.tb bactericidal burden and histopathological inflammation in mice. Here, we asked which genes in human inflammatory macrophages are affected upon infection with M.tb and how would potential changes impact the functional state of macrophages. We used a flow cytometry sorting system which can distinguish the dead and alive states of M.tb harbored in human monocyte-derived macrophages (MDM). We found that the expression of cyclooxygenase-2 and microsomal prostaglandin E2 synthase (mPGES)-1 increased significantly in tagRFP+ MDM which were infected with alive M.tb. After exposure of polarized M1-MDM to M.tb (H37Rv strain)-conditioned medium (MTB-CM) or to the M.tb-derived 19-kD antigen, the production of PGE2 and pro-inflammatory cytokines increased 3- to 4-fold. Upon treatment of M1-MDM with SASP, the MTB-CM-induced expression of COX-2 and the release of COX products and cytokines decreased. Elevation of PGE2 in M1-MDM upon MTB-CM stimulation and modulation by SASP correlated with the activation of the NF-κB pathway. Together, infection of human macrophages by M.tb strongly induces COX-2 and mPGES-1 expression along with massive PGE2 formation which is abrogated by the anti-inflammatory drug SASP.